Pseudocapacitance-boosted ultrafast and stable Na-storage in NiTe2 coupled with N-doped carbon nanosheets for advanced sodium-ion half/full batteries. Issue 46 (17th November 2021) - Han, Xu; Jiang, Qilei; Zhang, Mengling; Qin, Zheng; Geng, Hongbo; Sun, Chencheng; Gu, Hongwei
Abstract : Developing high-rate and durable anode materials for sodium-ion batteries (SIBs) is still a challenge because of the larger ion radius of sodium compared with the lithium ion during charge–discharge processes. Abstract : Developing high-rate and durable anode materials for sodium-ion batteries (SIBs) is still a challenge because of the larger ion radius of sodium compared with the lithium ion during charge–discharge processes. Herein, NiTe2 coupled with N-doped carbon (NiTe2 /NC) hexagonal nanosheets has been fabricated through a solvothermal and subsequent carbonisation strategy. This unique hexagonal nanosheet structure offers abundant active sites and contact area to the electrolyte, which could shorten the Na + diffusion path. The heterostructured N-doping carbon improves the electrochemical conductivity and accelerates the kinetics of Na + transportation. Electrochemical analysis shows that the charge–discharge process is controlled by the pseudocapacitive behavior thus leading to high-rate capability and long lifespan in half batteries. As expected, high capacities of 311 mA h g −1 to 217 mA h g −1 at 5 A g −1 to 10 A g −1 are maintained after 800 and 1200 cycles, respectively. Furthermore, a full battery equipped with a Na3 V2 (PO4 )2 O2 F cathode and a NiTe2 /NC anode offers a maximum energy density of 104 W h kg −1 and a maximum power density of 9116 W kg −1 . The results clearly show that the NiTe2 /NC hexagonal nanosheet with superior Na storage properties is an advanced new material for energy storage systems.